The Effect of Return on Equity, Debt Equity Ratio, and Dividend Payout Ratio on Stock Returns in Companies in the Energy Sector - Muhammad, Muhammad; Meirisa, Faradila (Jurnal Multidisiplin Sahombu, 2025)
This study analyzes the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), and Dividend Payout Ratio (DPR) on Stock Returns in energy sector companies on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. By using hypothesis testing, the research sample consisted of 22 companies. The results showed that ROE had a positive and significant effect, DER had no significant negative effect, and DPR had a negative and significant effect on Stock Returns. Simultaneously, these three variables have a significant influence with an Adjusted R² of 61.3%, indicating that other factors also affect Stock Returns.